COL4A1-Related Disease: Raised Creatine Kinase and Cerebral Calcification as Useful Pointers - Tonduti, Davide; Pichiecchio, Anna; La Piana, Roberta; Livingston, John H.; Doherty, Daniel A.; Majumdar, Anirban; Tomkins, Susan; Mine, Manuele; Ceroni, Mauro; Ricca, Ivana; Balottin, Umberto; Orcesi, Simona (Neuropediatrics, 2012)
Background Mutations in COL4A1 are responsible for a spectrum of clinical phenotypes characterized by neurological, ocular, and renal involvement. Neurological features are the most prominent but as such are rather nonspecific.Case Presentation Here, we report three new cases that, like five patients we previously described, show the novel common finding of raised creatine kinase (CK) concentration.Conclusion Raised CK concentration, in addition to intracranial calcification, is to be considered another useful pointer to a final diagnosis of COL4A1-related disease.
Keywords: COL4A1; cerebral calcification; creatine kinase; cataract